Weak solvation gel electrolyte and preparation method and application thereof

By using in-situ polymerization technology of weakly solvated electrolytes and double bond monomers in lithium metal batteries, gel electrolytes with high interfacial compatibility and cyclic stability are formed, and the problems of poor interfacial compatibility under large-face capacity lithium deposition and high voltage are solved, and more efficient lithium metal battery performance is achieved.

CN119905652APending Publication Date: 2025-04-29NANKAI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510069583.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-16
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

The existing gel electrolytes cannot adapt to dendrite growth caused by large-face capacity lithium deposition and poor interface compatibility with commercial cathode materials at high voltages.

Method used

A weakly solvated electrolyte and a polymerized double bond monomer are used to form a gel electrolyte in a lithium metal battery through in situ polymerization. The double lithium salt decomposes on the surface of the positive electrode to form a stable interface layer, and a weak solvated solvent is used to construct an anion-rich solvated structure.

Benefits of technology

It improves the positive and negative interface compatibility, cycle stability and safety of lithium metal batteries, extends the cycle life of the battery, and shows better voltage tolerance and wider electrochemical window at high voltages.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119905652A_ABST
    Figure CN119905652A_ABST
Patent Text Reader

Abstract

The invention discloses a weak-solvation gel electrolyte as well as a preparation method and application thereof, and relates to the technical field of gel electrolytes. According to the method, a weak solvation electrolyte and a monomer are uniformly mixed, and the electrolyte is bound in a polymer network through thermal initiation polymerization to form the gel electrolyte. The stability of a positive electrode interface film is guaranteed through matching of double lithium salts, meanwhile, an anion-rich solvation structure is constructed by the weak solvation solvent, and formation of a firm and stable negative electrode interface layer is promoted. The gel electrolyte prepared by the invention has relatively high ionic conductivity, good positive and negative electrode interface compatibility and a wide electrochemical window. Due to the adoption of the thermal initiation in-situ polymerization technology, the preparation method is simple and has large-scale application potential, and the cycle life and the cycle performance can be improved by matching the lithium metal battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of gel electrolytes, and in particular to a method for preparing a gel quasi-solid electrolyte and application thereof in a lithium metal battery. Background Art

[0002] Lithium metal batteries (LMBs) have a high theoretical specific capacity (3860 mAh g -1 ) and low oxidation potential (-3.04V compared to hydrogen electrode) as the negative electrode, lithium metal has great application prospects in the fields of new energy vehicles and energy storage power stations, and has been widely used in battery systems by researchers recently. Commercial positive electrode (LiFePO 4 、LiCoO 2 、xLi 2 MnO 3 ·(1-x)LiMO 2 (LRMO, etc.) have a high discharge platform and a large material tap density, and are considered to be ideal for the next generation of energy storage systems. However, transition metal oxide positive electrode materials such as lithium-rich manganese-based materials are prone to side reactions in the electrolyte during cycling, which deteriorates the electrolyte / positive electrode interface. At the same time, the dissolution of transition metals can also cause serious lattice distortion, further reducing battery performance. Solid-state LMBs can fundamentally avoid the problem of transition metal dissolution, but the interface problems between the electrode and the electrolyte caused by solid-solid contact and the low room temperature ionic conductivity hinder the development of solid-state LMBs. Quasi-solid gel electrolytes better balance the above relationship. Gel electrolytes (GPE) use polymers to bind electrolytes containing lithium salts and solvents in polymer segments. They have high room temperature ionic conductivity and can improve battery safety.

[0003] In order to further develop the energy storage advantages of lithium batteries, high loading (>60mg cm -2 ) pole piece and lithium negative electrode to assemble soft-pack batteries, but the large-area capacity lithium deposition / stripping process also brings great challenges to the electrolyte / negative electrode interface. On the other hand, in order to avoid side reactions between the electrolyte and the positive electrode material, an electrolyte / positive electrode interface layer with good chemical stability is also very important. Therefore, constructing a GPE system that is compatible with positive and negative electrodes under high voltage is conducive to the realization of long-life and high-energy-density lithium metal batteries. Using solvents with weak solvating properties instead of classical strong solvating solvents in GPE can construct more anion-rich solvation structures in the system, thereby promoting the decomposition of salt anions at the negative electrode to form a stronger and more stable interface layer. At the same time, lithium salts (such as LiBF) that are easy to decompose on the positive electrode side to form a stable interface film are used. 4 , LiDFOB) helps to improve the compatibility of GPE and the positive electrode. However, the weak solvating solvent itself is Li-phobic. + The characteristics will improve Li to a certain extent +Migration energy barriers and reduced conductivity. Therefore, it is urgent to solve the above-mentioned problems of interface compatibility and bulk transport kinetics. Summary of the invention

[0004] The purpose of the present invention is to solve the problem that the existing gel electrolyte cannot adapt to the dendrite growth caused by large-area capacity lithium deposition and has poor interface compatibility with commercial positive electrode materials under high voltage, and to provide a gel electrolyte and a preparation method thereof.

[0005] To achieve the above objectives, the present invention provides the following technical solutions:

[0006] In a first aspect, the present invention provides a gel electrolyte comprising a weak solvent electrolyte and a double-bond monomer having polymerization activity, wherein the mass ratio of the monomer to the weak solvent electrolyte is 1:5.6-12.3.

[0007] In some embodiments, the weakly solvated electrolyte is composed of one or more lithium salts (including but not limited to LiPF 6 , LiDFOB) and dissolved in a mixed solution of fluoroethylene carbonate (FEC) and methyl trifluoropropionate (MTFP); the volume ratio of fluoroethylene carbonate (FEC) to methyl trifluoropropionate (MTFP) is 1:0.33~3.

[0008] In some embodiments, the polymer matrix is ​​a network polymer composed of 2,2,3,4,4,4-hexafluorobutyl acrylate (HFBA) and ethoxylated trimethylolpropane triacrylate (ETPTA), or a linear or cross-linked polymer composed of acrylic monomers and / or epoxy monomers. Preferably, in the precursor solution, based on the weight of the weakly solvated electrolyte as 100%, the amount of HFBA is 5-10%, and the amount of ETPTA is 2.5-5%.

[0009] In some embodiments, in addition to the polymerizable monomer and the weakly solvated electrolyte, an initiator azobisisobutyronitrile (AIBN) is also included. In the precursor solution, the amount of azobisisobutyronitrile is 0.30-0.50% based on the weight of the mixed solution of the weakly solvated electrolyte and the polymerizable monomer as 100%.

[0010] In a second aspect, the present invention also provides a method for preparing the gel electrolyte in the above embodiment, comprising the following steps:

[0011] S1. Preparation of precursor solution: dissolve the thermal initiator in the mixed solution of the above-mentioned polymerization monomer and weak solvent electrolyte, and stir for 10-20 minutes.

[0012] S2. Preparation of in-situ polymerized gel electrolyte: When assembling the battery, the precursor solution is used to replace the electrolyte and is dripped onto both sides of the Celgard diaphragm. The assembled battery is pressed and placed for 12-18 hours and then heated in a forced air oven.

[0013] In some embodiments, when the precursor solution is used, the in-situ polymerization is performed at a temperature of 50 to 60° C., and the polymerization time is 2 to 6 hours.

[0014] A third aspect of the present invention provides a lithium metal battery, which uses the gel electrolyte in the above embodiment to improve the positive and negative electrode interface compatibility, cycle stability and safety of the lithium-sulfur battery.

[0015] Compared with the prior art, this application has the following beneficial effects:

[0016] The present invention adopts an in-situ polymerization method. After adding the precursor solution to the battery, heating can initiate polymerization to form a gel electrolyte, in which the lithium salt can decompose on the positive electrode surface to form a good electrolyte / positive electrode interface layer with chemical stability. A weak solvating solvent is used instead of a classical strong solvating solvent to form an anion-rich solvation structure in the system, forming a stable and strong interface layer at the negative electrode, and promoting the uniform deposition / stripping of Li. The prepared gel electrolyte has the property of being compatible with both positive and negative electrodes, and improves the cycle life of lithium metal batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0018] Figure 1 SEM images of the surface (a) and cross-section (b) of Example 1.

[0019] Figure 2 1 is a comparison chart of the room temperature ionic conductivity of the gel electrolytes of Example 1 and Comparative Example 1.

[0020] Figure 3 This is a leakage current test diagram of the gel electrolyte of Example 1-3.

[0021] Figure 4 The linear sweep voltammetry (LSV) test diagram of the gel electrolyte of Examples 1-3.

[0022] Figure 5 This is a leakage current test diagram of the gel electrolyte of Examples 1, 4-7.

[0023] Figure 6 For Example 1, 4-7 gel electrolyte at 0.5 mA cm -2 and 0.5 mAh cm -2 Coulombic efficiency diagram of Li||Cu asymmetric battery under different conditions.

[0024] Figure 7 This is a cycling performance diagram of the lithium-rich manganese-based lithium battery with gel electrolyte of Example 1, 4-6 at a rate of 0.2C.

[0025] Figure 8 This is a leakage current test diagram of the gel electrolyte of Examples 1, 8-9.

[0026] Fig. 9 For Example 1, 8-9, the gel electrolyte is at 0.5 mA cm -2 and 0.5 mAh cm -2 Coulombic efficiency diagram of Li||Cu asymmetric battery under different conditions.

[0027] Fig.10 This is a cycling performance diagram of the lithium-rich manganese-based lithium battery with gel electrolyte of Example 1, 8-9 at a rate of 0.2C.

[0028] Fig.11 The leakage current test diagram of the gel electrolyte of Example 1 and Comparative Example 1.

[0029] Fig.12 These are LSV test diagrams of the gel electrolytes of Example 1 and Comparative Example 1.

[0030] Fig.13 The infrared spectra of the gel electrolytes of Example 1 and Comparative Example 1 (a) and the peak analysis diagram (b) below.

[0031] Fig.14 The Li||Cu asymmetric battery with gel electrolyte of Example 1 (a) and Comparative Example (b) at 0.5 mA cm -2 and 2mAh cm -2 Deposition morphology of Li on Cu foil after one cycle of discharge under different conditions.

[0032] Fig.15 The coulombic efficiency diagram of the Li||Cu asymmetric battery with gel electrolyte of Example 1 and Comparative Example 1.

[0033] Fig.16 The graph is a cycle performance diagram of lithium-rich manganese-based lithium batteries with gel electrolytes of Example 1 and Comparative Example 1 at a rate of 0.2C. DETAILED DESCRIPTION

[0034] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0035] The present invention provides a gel electrolyte, comprising a weak solvent electrolyte and a double-bond monomer with polymerization activity, wherein the mass ratio of the monomer to the weak solvent electrolyte is 1:5.6-12.3. The polymer matrix is ​​a network polymer composed of 2,2,3,4,4,4-hexafluorobutyl acrylate (HFBA) and ethoxylated trimethylolpropane triacrylate (ETPTA), or a linear or cross-linked polymer composed of acrylic monomers and / or epoxy monomers. In addition to the polymerizable monomers and the weak solvent electrolyte, an initiator azobisisobutyronitrile (AIBN) is also included.

[0036] The following embodiments of the present invention also provide a method for preparing the above-mentioned gel electrolyte, specifically:

[0037] Example 1

[0038] A method for preparing a gel quasi-solid electrolyte comprises the following steps:

[0039] S1. Preparation of precursor solution:

[0040] 1M LiPF 6 and 0.2M LiDFOB are dissolved in a mixed solution of FEC and MTFP, the volume ratio of FEC and MTFP is 1:3, based on the weight of the weakly solvated electrolyte being 100%, the amount of HFBA is 5%, and the amount of ETPTA is 2.5%. A thermal initiator is dissolved in the mixed solution of the above-mentioned polymerizing monomer and the weakly solvated electrolyte, and stirred for 10-20 minutes, based on the weight of the mixed solution of the weakly solvated electrolyte and the polymerizing monomer being 100%, the amount of the azobisisobutyronitrile is 0.5%.

[0041] S2. Preparation of in-situ polymerized gel electrolyte: When assembling the battery, the precursor solution is used to replace the electrolyte and is dripped onto both sides of the Celgard separator. The assembled battery is pressed and placed for 12 hours and then heated in a forced air oven at 60°C for 2 hours.

[0042] Example 2

[0043] A method for preparing a gel quasi-solid electrolyte comprises the following steps:

[0044] S1. Preparation of precursor solution:

[0045] 1M LiPF6 and 0.2M LiDFOB are dissolved in a mixed solution of FEC and MTFP, the volume ratio of FEC and MTFP is 1:3, based on the weight of the weak solvating electrolyte being 100%, the amount of trifluoroethyl acrylate (TFEA) is 5%, and the amount of ETPTA is 2.5%. A thermal initiator is dissolved in the mixed solution of the above-mentioned polymerizing monomer and the weak solvating electrolyte, and stirred for 10-20 minutes, based on the weight of the mixed solution of the weak solvating electrolyte and the polymerizing monomer being 100%, the amount of the azobisisobutyronitrile is 0.5%.

[0046] S2. Preparation of in-situ polymerized gel electrolyte: When assembling the battery, the precursor solution is used to replace the electrolyte and is dripped onto both sides of the Celgard separator. The assembled battery is pressed and placed for 12 hours and then heated in a forced air oven at 60°C for 2 hours.

[0047] Example 3

[0048] A method for preparing a gel quasi-solid electrolyte comprises the following steps:

[0049] S1. Preparation of precursor solution:

[0050] 1M LiPF 6 and 0.2M LiDFOB are dissolved in a mixed solution of FEC and MTFP, the volume ratio of FEC and MTFP is 1:3, based on the weight of the weak solvation electrolyte being 100%, the amount of 2,2,3,3,3-pentafluoropropyl acrylate (PFPA) is 5%, and the amount of ETPTA is 2.5%. A thermal initiator is dissolved in the mixed solution of the above-mentioned polymerizing monomer and the weak solvation electrolyte, and stirred for 10-20 minutes, based on the weight of the mixed solution of the weak solvation electrolyte and the polymerizing monomer being 100%, the amount of the azobisisobutyronitrile is 0.5%.

[0051] S2. Preparation of in-situ polymerized gel electrolyte: When assembling the battery, the precursor solution is used to replace the electrolyte and is dripped onto both sides of the Celgard separator. The assembled battery is pressed and placed for 12 hours and then heated in a forced air oven at 60°C for 2 hours.

[0052] Example 4

[0053] A method for preparing a gel quasi-solid electrolyte comprises the following steps:

[0054] S1. Preparation of precursor solution:

[0055] 0.6M LiPF 6and 0.6M LiDFOB are dissolved in a mixed solution of FEC and MTFP, the volume ratio of FEC and MTFP is 1:3, based on the weight of the weakly solvated electrolyte being 100%, the amount of HFBA is 5%, and the amount of ETPTA is 2.5%. A thermal initiator is dissolved in the mixed solution of the above-mentioned polymerizing monomer and the weakly solvated electrolyte, and stirred for 10-20 minutes, based on the weight of the mixed solution of the weakly solvated electrolyte and the polymerizing monomer being 100%, the amount of the azobisisobutyronitrile is 0.5%.

[0056] S2. Preparation of in-situ polymerized gel electrolyte: When assembling the battery, the precursor solution is used to replace the electrolyte and is dripped onto both sides of the Celgard separator. The assembled battery is pressed and placed for 12 hours and then heated in a forced air oven at 60°C for 2 hours.

[0057] Example 5

[0058] A method for preparing a gel quasi-solid electrolyte comprises the following steps:

[0059] S1. Preparation of precursor solution:

[0060] 1.2M LiPF 6 Dissolved in a mixed solution of FEC and MTFP, the volume ratio of FEC and MTFP is 1:3, based on the weight of the weakly solvated electrolyte being 100%, the amount of HFBA is 5%, and the amount of ETPTA is 2.5%. The thermal initiator is dissolved in the mixed solution of the above-mentioned polymerized monomer and the weakly solvated electrolyte, and stirred for 10-20 minutes, based on the weight of the mixed solution of the weakly solvated electrolyte and the polymerized monomer being 100%, the amount of the azobisisobutyronitrile is 0.5%.

[0061] S2. Preparation of in-situ polymerized gel electrolyte: When assembling the battery, the precursor solution is used to replace the electrolyte and is dripped onto both sides of the Celgard separator. The assembled battery is pressed and placed for 12 hours and then heated in a forced air oven at 60°C for 2 hours.

[0062] Example 6

[0063] A method for preparing a gel quasi-solid electrolyte comprises the following steps:

[0064] S1. Preparation of precursor solution:

[0065] 1.2M LiDFOB is dissolved in a mixed solution of FEC and MTFP, the volume ratio of FEC and MTFP is 1:3, based on the weight of the weakly solvated electrolyte being 100%, the amount of HFBA is 5%, and the amount of ETPTA is 2.5%. A thermal initiator is dissolved in the mixed solution of the above-mentioned polymerizing monomer and the weakly solvated electrolyte, and stirred for 10-20 minutes, based on the weight of the mixed solution of the weakly solvated electrolyte and the polymerizing monomer being 100%, the amount of the azobisisobutyronitrile is 0.5%.

[0066] S2. Preparation of in-situ polymerized gel electrolyte: When assembling the battery, the precursor solution is used to replace the electrolyte and is dripped onto both sides of the Celgard separator. The assembled battery is pressed and placed for 12 hours and then heated in a forced air oven at 60°C for 2 hours.

[0067] Example 7

[0068] A method for preparing a gel quasi-solid electrolyte comprises the following steps:

[0069] S1. Preparation of precursor solution:

[0070] 1.2M LiFSI is dissolved in a mixed solution of FEC and MTFP, the volume ratio of FEC and MTFP is 1:3, based on the weight of the weakly solvated electrolyte being 100%, the amount of HFBA is 5%, and the amount of ETPTA is 2.5%. A thermal initiator is dissolved in the mixed solution of the above-mentioned polymerized monomer and the weakly solvated electrolyte, and stirred for 10-20 minutes, based on the weight of the mixed solution of the weakly solvated electrolyte and the polymerized monomer being 100%, the amount of azobisisobutyronitrile is 0.5%.

[0071] S2. Preparation of in-situ polymerized gel electrolyte: When assembling the battery, the precursor solution is used to replace the electrolyte and is dripped onto both sides of the Celgard separator. The assembled battery is pressed and placed for 12 hours and then heated in a forced air oven at 60°C for 2 hours.

[0072] Example 8

[0073] A method for preparing a gel quasi-solid electrolyte comprises the following steps:

[0074] S1. Preparation of precursor solution:

[0075] 1M LiPF 6and 0.2M LiDFOB are dissolved in a mixed solution of FEC and MTFP, the volume ratio of FEC and MTFP is 1:1, based on the weight of the weakly solvated electrolyte being 100%, the amount of HFBA is 5%, and the amount of ETPTA is 2.5%. A thermal initiator is dissolved in the mixed solution of the above-mentioned polymerizing monomer and the weakly solvated electrolyte, and stirred for 10-20 minutes, based on the weight of the mixed solution of the weakly solvated electrolyte and the polymerizing monomer being 100%, the amount of the azobisisobutyronitrile is 0.5%.

[0076] S2. Preparation of in-situ polymerized gel electrolyte: When assembling the battery, the precursor solution is used to replace the electrolyte and is dripped onto both sides of the Celgard separator. The assembled battery is pressed and placed for 12 hours and then heated in a forced air oven at 60°C for 2 hours.

[0077] Example 9

[0078] A method for preparing a gel quasi-solid electrolyte comprises the following steps:

[0079] S1. Preparation of precursor solution:

[0080] 1M LiPF 6 and 0.2M LiDFOB are dissolved in a mixed solution of FEC and MTFP, the volume ratio of FEC and MTFP is 3:1, based on the weight of the weakly solvated electrolyte being 100%, the amount of HFBA is 5%, and the amount of ETPTA is 2.5%. A thermal initiator is dissolved in the mixed solution of the above-mentioned polymerizing monomer and the weakly solvated electrolyte, and stirred for 10-20 minutes, based on the weight of the mixed solution of the weakly solvated electrolyte and the polymerizing monomer being 100%, the amount of the azobisisobutyronitrile is 0.5%.

[0081] S2. Preparation of in-situ polymerized gel electrolyte: When assembling the battery, the precursor solution is used to replace the electrolyte and is dripped onto both sides of the Celgard separator. The assembled battery is pressed and placed for 12 hours and then heated in a forced air oven at 60°C for 2 hours.

[0082] Comparative Example 1

[0083] A method for preparing a gel quasi-solid electrolyte comprises the following steps:

[0084] S1. Preparation of precursor solution:

[0085] 1M LiPF 6and 0.2M LiDFOB are dissolved in a mixed solution of FEC and EMC, the volume ratio of FEC and EMC is 1:1, based on the weight of the electrolyte being 100%, the amount of HFBA is 5%, and the amount of ETPTA is 2.5%. A thermal initiator is dissolved in the mixed solution of the above-mentioned polymerized monomer and electrolyte, and stirred for 10-20 minutes, based on the weight of the mixed solution of the electrolyte and the polymerized monomer being 100%, the amount of the azobisisobutyronitrile is 0.5%.

[0086] S2. Preparation of in-situ polymerized gel electrolyte: When assembling the battery, the precursor solution is used to replace the electrolyte and is dripped onto both sides of the Celgard separator. The assembled battery is pressed and placed for 12 hours and then heated in a forced air oven at 60°C for 2 hours.

[0087] Application Examples

[0088] The gel electrolyte prepared in the embodiment was used as the test electrolyte, commercial lithium-rich manganese-based powder was used as the positive electrode (the mass ratio of lithium-rich manganese-based, conductive agent SuperP, and binder PVDF was 8:1:1), and a lithium sheet was used as the negative electrode. CR2032 button batteries were assembled in a glove box filled with argon. The following is the material characterization and electrochemical performance test of the selected specific embodiments.

[0089] Figure 1 The SEM images of the surface (a) and cross section (b) of Example 1 show that the electrolyte is evenly formed on the surface of the Celgard diaphragm, and the surface is smooth and flat. The cross section does not show the classic polypropylene segment morphology of the Celgard diaphragm, but a complete and uniform plane, indicating that the precursor solution has completely infiltrated the interior of the diaphragm and polymerized to form a gel electrolyte.

[0090] Figure 2 The room temperature ionic conductivity of Example 1 is compared with that of Comparative Example 1, wherein the room temperature ionic conductivity of Example 1 is 0.367 mS cm -1 , compared with 0.532 mS cm in Comparative Example 1 -1 This is because the solvent with weak solvation properties was used in Example 1, which + The binding effect is weak, so the conductivity decreases, but it is still higher than 0.1mS cm -1 , ensuring that the battery matching this electrolyte can operate normally.

[0091] Figure 3 The leakage current test diagram of the gel electrolyte of Examples 1-3 shows that under medium voltage level (4.6-5.2V), Examples 1-3 have smaller leakage currents, while under high voltage conditions (>5.2V), Example 1 has an even smaller current, proving that it has better voltage tolerance.

[0092] Figure 4 The linear sweep voltammetry (LSV) test diagrams of the gel electrolytes of Examples 1 to 3 show that the electrochemical windows of Examples 1 to 3 are 5.4, 4.5 and 4.7 V, respectively, proving that the gel electrolyte of Example 1 has a wider electrochemical window.

[0093] Figure 5 The leakage current test diagram of the gel electrolyte of Examples 1, 4-7 is shown. It can be found that at a medium voltage level (4.6-5.2V), the current of Example 7 is relatively large, while Examples 1, 5, and 6 all have relatively small leakage currents, indicating that the electrolyte has very few side reactions under high voltage, proving that the two lithium salts in Example 1 alone or in combination have high voltage tolerance.

[0094] Figure 6 For Example 1, 4-7 gel electrolyte at 0.5 mA cm -2 and 0.5 mAh cm -2 Coulombic efficiency diagram of Li||Cu asymmetric battery under conditions. It can be found that Example 7 has the best cycle stability, but its instability under high voltage limits its application in lithium-rich manganese-based lithium batteries. The average coulombic efficiency of Example 6 in the 2nd to 65th cycles is 95.94%, which is far inferior to Example 5, which can run stably for 500 cycles, and the average coulombic efficiency in the 300th to 500th cycles is 97.06%. However, Example 1, which combines the two lithium salts, has a better coulombic efficiency, with an average coulombic efficiency of 97.62% for 375 cycles. It proves that the combination of double lithium salts with weak solvating solvents can promote Li + uniform deposition / stripping behavior, thereby improving the Coulombic efficiency on the negative electrode side.

[0095] Figure 7 The cycle performance diagram of the lithium-rich manganese-based lithium battery with gel electrolyte of Examples 1, 4-6 at a rate of 0.2C is shown. The 45-cycle capacity retention rate of Example 5 is 68.5%, while both Examples 6 and 7 have a capacity retention rate greater than 90%. Example 1 has the best cycle performance, proving that the dual salt system can significantly improve the cycle stability of lithium-rich manganese-based lithium batteries.

[0096] Figure 8 The leakage current test of the gel electrolytes of Examples 1, 8-9 shows that, since increasing the proportion of MTFP will increase the number of fluorine-containing groups in the system, compared with Examples 8 and 9, Example 1 has a smaller leakage current.

[0097] Fig. 9 For Example 1, 8-9, the gel electrolyte is at 0.5 mA cm -2 and 0.5 mAh cm -2Coulombic efficiency diagram of Li||Cu asymmetric battery under the conditions. Since the proportion of the weak solvating solvent MTFP in Example 1 is relatively large, a solvation configuration rich in anions can be better formed at the negative electrode, and the coulombic efficiency on the negative electrode side can be improved by forming a relatively stable interface layer at the negative electrode.

[0098] Fig.10 The cycle performance diagram of the lithium-rich manganese-based lithium battery with gel electrolyte of Examples 1 and 8-9 at a rate of 0.2C. The capacity retention rates of Examples 8 and 9 after 50 cycles were 85.6% and 84.7% respectively, and Example 1 used a suitable weak solvating solvent ratio to ensure the stability of the positive electrode interface layer while taking into account the negative electrode Li + The deposition / stripping stability is greatly improved, thus achieving better cycle performance.

[0099] Fig.11 The leakage current test diagram of the gel electrolyte of Example 1 and Comparative Example 1 is shown. Example 1 has a significantly smaller leakage current under high voltage (>5.2V), which proves better voltage tolerance under high voltage.

[0100] Fig.12 The LSV test diagrams of the gel electrolytes of Example 1 and Comparative Example 1 are shown. The electrochemical window of Example 1 is 5.4V, which is higher than 4.0V of Comparative Example 1. Since MTFP and HFBA in the system provide more F-containing groups, Example 1 has a wider electrochemical window.

[0101] Fig.13 The infrared spectra of the gel electrolytes of Example 1 and Comparative Example 1 (a) and the analysis of the C=O peaks at 1800 and 1700 cm-1 (b) are shown. It can be found that the peaks near 1735 cm-1 of both disappeared after polymerization, proving that both gel electrolytes have been completely polymerized. At the same time, it was found that the coupled C=O peaks of HFBA and ETPTA in Comparative Example 1 were at 1747.65 cm-1. -1 , while the corresponding peak position of the embodiment is 1742.88cm -1 The C=O bond of the polymerized monomer in Example 1 undergoes an obvious red shift, which also proves that Li + The bond with C=O in the polymer is weak, and a weakly solvated gel electrolyte is successfully constructed.

[0102] Fig.14 The Li||Cu asymmetric battery with gel electrolyte of Example 1 (a) and Comparative Example (b) at 0.5 mA cm -2 and 2mAh cm -2The deposition morphology of Li on the Cu foil after one cycle of discharge under the same conditions. It can be found that the Li in Example 1 is uniform and dense, with small gaps, while the dendrites in Comparative Example 1 are obvious, and Li is unevenly deposited on the Cu foil surface to form a loose and porous structure.

[0103] Fig.15 The coulombic efficiency diagram of the Li||Cu asymmetric battery of the gel electrolyte of Example 1 and Comparative Example 1 is shown. Since the addition of the weak solvating solvent improves the solvation structure of the system, Li+ and salt anions are more closely combined, which is conducive to forming a more stable electrolyte / negative electrode interface layer. The average coulombic efficiency of Example 1 in 25-350 cycles can reach 97.56%, which is better than Comparative Example 1 in both coulombic efficiency and cycle performance.

[0104] Fig.16 The cycle performance diagram of the lithium-rich manganese-based lithium battery with gel electrolyte of Example 1 and Comparative Example 1 at 0.2C rate. The capacity retention rate of 55 cycles in Example 1 can reach 96.17, which is much higher than 82.03% of Comparative Example 1 under the same conditions. In general, the use of weak solvating solvents instead of classic strong solvating solvents to prepare gel electrolytes can form a positive electrode / electrolyte interface layer with higher chemical stability while ensuring the coulombic efficiency of the negative electrode, thereby better improving the cycle stability of the positive electrode.

[0105] Based on the above embodiments, the present invention provides a weakly solvated gel electrolyte and a method for preparing the gel electrolyte. The present invention ensures the stability of the positive electrode interface film by matching a double lithium salt, and at the same time, the weakly solvated solvent constructs an anion-rich solvation structure to promote the formation of a strong and stable negative electrode interface layer. The gel electrolyte prepared by the present invention has high ionic conductivity, good compatibility between the positive and negative electrodes and a wide electrochemical window. Due to the use of thermally initiated in-situ polymerization technology, the preparation method is simple and has the potential for large-scale application, and matching lithium metal batteries can improve the cycle life and cycle performance. The embodiments of the present invention do not exhaust all the options in the technical scheme of the present invention, and the technical scheme composed of other selection methods that are not used as embodiments has the same technical effect as the disclosed embodiments. Further, the present invention verifies through comparative examples that the present invention has better voltage tolerance and a wider electrochemical window at high voltage, and at the same time, the gel electrolyte structure obtained by the present invention, the coulomb efficiency of the Li||Cu asymmetric battery, and the cycle stability of the positive electrode have achieved ideal technical effects.

[0106] It should be further explained that the above implementation modes are only used to understand the technical solution of the present invention, and are not used to limit the protection scope of the present invention. Any obvious adjustments and modifications made to the technical concept of the present invention should also fall within the protection scope of the present invention.

Claims

1. A gel electrolyte, characterized in that: The method comprises a weak solvent electrolyte and a double-bond monomer having polymerization activity, wherein the mass ratio of the monomer to the weak solvent electrolyte is 1:5.6-12.3; The weakly solvated electrolyte is composed of one or more lithium salts and is dissolved in a mixed solution of fluoroethylene carbonate FEC and methyl trifluoropropionate MTFP.

2. The gel electrolyte according to claim 1, characterized in that The lithium salt includes but is not limited to one of lithium hexafluorophosphate LiPF6 and lithium difluorooxalatoborate LiDFOB; the volume ratio of fluoroethylene carbonate FEC and methyl trifluoropropionate MTFP is 1:0.33-3.

3. The gel electrolyte according to claim 1, characterized in that The polymer matrix is ​​a network polymer composed of 2,2,3,4,4,4-hexafluorobutyl acrylate HFBA and ethoxylated trimethylolpropane triacrylate ETPTA, or a linear or cross-linked polymer composed of acrylic monomers and / or epoxy monomers; in the precursor solution, based on the weight of the weakly solvated electrolyte being 100%, the amount of HFBA is 5-10%, and the amount of ETPTA is 2.5-5%.

4. The gel electrolyte according to claim 1, characterized in that The gel electrolyte also includes an initiator azobisisobutyronitrile AIBN. In the precursor solution, based on the weight of the mixed solution of the weak solvent electrolyte and the polymerized monomer as 100%, the amount of the azobisisobutyronitrile is 0.30-0.50%.

5. A method for preparing the gel electrolyte according to any one of claims 1 to 4, characterized in that: The steps include: S1. Preparation of precursor solution: dissolving the thermal initiator in a mixed solution of polymerization monomer and weakly solvent electrolyte, and stirring for 10-20 minutes; S2. Preparation of in-situ polymerized gel electrolyte: When assembling the battery, the precursor solution is used to replace the electrolyte and is dripped onto both sides of the Celgard diaphragm. The assembled battery is pressed and placed for 12-18 hours and then heated in a forced air oven.

6. The method for preparing the gel electrolyte according to claim 5, characterized in that: The in-situ polymerization is carried out at a temperature of 50 to 60° C. and a polymerization time of 2 to 6 hours.

7. A lithium metal battery, characterized in that: The gel electrolyte according to any one of claims 1 to 4 is used.